Roxadustat, a Hypoxia-Inducible Factor 1α Activator, Attenuates Both Long- and Short-Term Alcohol-Induced Alcoholic Liver Disease - Gao, Yongyao; Jiang, Xiaomeng; Yang, Daigang; Guo, Wentong; Wang, Dandan; Gong, Ke; Peng, Ying; Jiang, Hong; Shi, Cunyuan; Duan, Yajun; Chen, Yuanli; Han, Jihong; et al. (Frontiers in Pharmacology, 2022)
Alcoholic liver disease (ALD) is a worldwide healthcare problem featured by inflammation, reactive oxygen species (ROS) and lipid dysregulation. Roxadustat is used for chronic kidney disease anemia treatment. As a specific inhibitor of prolyl hydroxylase, it can maintain high levels of hypoxia-inducible factor 1α (HIF-1α), through which it can further influence many important pathways, including the three featured in ALD. However, its effects on ALD remains to be elucidated. In this study, we used the chronic and acute ALD mouse models to investigate the protective effects of roxadustat in vivo. Our results showed that long- and short-term alcohol exposure caused rising activities of serum transaminases, liver lipid accumulation and morphology changes, which were reversed by roxadustat. Roxadustat reduced fatty liver was mainly contributed by reducing sterol-responsive element binding protein 1c (SREBP1c) pathway, and enhancing β-oxidation through inducing peroxisome proliferator-activated receptor α (PPARα) and carnitine palmitoyltransferase 1A (CPT1A) expression. Long-term alcohol treatment induced the infiltration of monocytes/macrophage to hepatocytes, as well as inflammatory cytokines expression, which were also blocked by roxadustat. Moreover, roxadustat attenuated alcohol-caused ROS generation in liver of those two mouse models mainly by reducing cytochrome P450 2E1 (CYP2E1) and enhancing superoxidase dismutase 1 (SOD1) expression. In vitro, we found roxadustat reduced inflammation and lipid accumulation mainly via HIF-1α regulation. Taken together, our study demonstrates that activation of HIF-1α can ameliorate ALD, which is contributed by reduced hepatic lipid synthesis, inflammation and oxidative stress. This study suggests roxadustat could be a potential drug for ALD treatment.